2016
DOI: 10.2305/iucn.ch.2016.16.en
|View full text |Cite
|
Sign up to set email alerts
|

Water management and stewardship : taking stock of corporate water behaviour

Abstract: IUCN is a membership Union uniquely composed of both government and civil society organisations. It provides public, private and non-governmental organisations with the knowledge and tools that enable human progress, economic development and nature conservation to take place together.Created in 1948, IUCN is now the world's largest and most diverse environmental network, harnessing the knowledge, resources and reach of more than 1,300 Member organisations and some 16,000 experts. It is a leading provider of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Specifically, the report referred to measures whose adoption would require behavior change from millions of farmers andindustrial and domestic water users. Seven years later, Newborne and Dalton (2016) found there had been little evolution by companies from business as usual on water. Their report, described as 'taking stock' of corporate action on water management and water stewardship, found that, while corporate concern about water risks was evident, companies interviewed in the study struggled to create a business case for action.…”
Section: A Known Problemmentioning
confidence: 99%
“…Specifically, the report referred to measures whose adoption would require behavior change from millions of farmers andindustrial and domestic water users. Seven years later, Newborne and Dalton (2016) found there had been little evolution by companies from business as usual on water. Their report, described as 'taking stock' of corporate action on water management and water stewardship, found that, while corporate concern about water risks was evident, companies interviewed in the study struggled to create a business case for action.…”
Section: A Known Problemmentioning
confidence: 99%
“…Water stewardship has emerged across the private sector as the best approach to enhance corporate management of water [5,31]. The approach requires a commitment from companies to the sustainable management of shared water resources in the public interest through collective action with other businesses, governments, non-government organisations (NGOs) and communities [29].…”
Section: Making the Paradigm Shift: Policy And Actionsmentioning
confidence: 99%
“…In reality, water stewardship as a formalised concept is relatively new being only a decade old. Considering the concept's relative infancy, most private sector companies are still in the early stages of its application, with implementation on the ground needing to catch-up with the high-level concepts [31].…”
Section: Making the Paradigm Shift: Policy And Actionsmentioning
confidence: 99%
“…Different types of businesses exist across sectors: the ability to make a change, whether through improving technological efficiencies in the supply chain or through their role in social/corporate responsibility, directly impacts the different resource systems and their future allocations. Businesses have an increasing stake in being better stewards of resources, perhaps water, which is a result of encountered disruptions due to water supply challenges [45]. "Government" is a series of constructs and processes that make laws and regulations, represented (in democratic societies) by legislative, judicial, and executive branches.…”
Section: Resource Systems and Players Differ And Interact Within And mentioning
confidence: 99%